Atypical initial presentations of Sjogren’s syndrome: a case series - Faiza Naeem; Salman Khurshid Imami; Saira Elaine Anwer Khan; Shabnam Batool; Muhammad Akmal; Yasir Mushtaq (Journal of the Pakistan Medical Association)
Primary Sjogren’s syndrome (pSS) typically presents with Sicca symptoms xerostomia and xeropthalmia. This study highlights atypical presentations of Primary Sjogren's syndrome posing diagnostic and therapeutic challenges.